Determinants of Rice Import in Asean Countries - Alfarkhan, Izwan; Wardani, Dyah Titis Kusuma (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
This research aims to analyze the influence of rice consumption rate, harvest area, consumer price index, and total quantity of cassava production on rice import in ASEAN countries period 2007 - 2017. Data are from secondary data, that is the panel data consists of time series data (obtained from 2007 to 2017) and cross section data are from eight selected ASEAN countries. The estimation is using Ordinary Least Squares Regression Analysis. The result shows that, rice consumption rate and consumer price index have a positive and significant effect to the rice import, harvest area has a positive and not significant effect on rice import and total quantity of cassava production have a negative and significant effect on rice import. The research is expected to give some insight in the design of industrial and import policies, parties. The policy recommendation goes to Indonesia, as an agrarian country, Indonesia should be able to minimize imports by utilizing large areas of agricultural land. This research recommends that the government maximizing land use to reduce imports, since Indonesia has a vast agricultural land. In addition, Indonesian people need to be encouraged to consume more cassava instead of consuming rice only for their staple food.